Lung cancer prediction with advanced graph neural networks - Moozhippurath, Bineesh; Natarajan, Jayapandian (Institute of Advanced Engineering and Science, 2025)
This research aims to enhance lung cancer prediction using advanced machine learning techniques. The major finding is that integrating graph convolutional networks (GCNs) with graph attention networks (GATs) significantly improves predictive accuracy. The problem addressed is the need for early and accurate detection of lung cancer, leveraging a dataset from Kaggle's